Pengaruh Faktor Spesifik Terhadap Profitabilitas Berdasarkan Kelompok Buku Bank di Indonesia - Uum Sholikhah Fitria; I Made Sudana (Forum Manajemen Indonesia (FMI), 2015)
This study aims to determine the influence of specific factors on bank BUKU groups in Indonesia. The sample was a conventional bank in 2013-2014. This study used multiple linear regression method. The dependent variable in this study are return on assets (ROA) and return on equity (ROE), while the independent variables used are size, operating efficiency (OE), capital adequacy ratio (CAR), credit risk (CR), asset management ( AM), and portfolio composition (PC). The Result from this study indicate that size has positive effect on ROA and ROE BUKU groups 1, 2, 3, and negative effect onROA and ROE on the group BUKU 4. Operating efficiency has negative effect on ROA and ROE in all BUKU groups. Capital adequacy ratio has negative effect on ROA and ROE in all BUKU groups, except on BUKU 3 has positive effect on ROA. Credit risk has negative effect on ROA and ROE in all BUKU groups. Asset management has positive effect on ROA and ROE BUKU 1,2, and 3, while on BUKU 4 has negative effect. Portfolio composition has negative effect on ROA and ROE BUKU group 1 and 2, and on BUKU 3 and 4 have positive effect. Keywords: Bank’s specific factors, profitability, BUKU groups of bank.